Principales biomarcadores moleculares en la caracterización de los tumores del sistema nervioso central - Báez, Alejandra; González Roffo, Alejandra; Gómez Escalante, José; Campero, Álvaro; Casas Parera, Ignacio (Revista Argentina de Neurocirugía, 2020)
The Classification of Tumors of the Central Nervous System of the WHO 2016 incorporates molecular biomarkers together with the classical histological characteristics, in an integrated diagnosis, in order to define different glioma entities with the highest possible accuracy. Studies of molecular profiles in the genome have revealed characteristic genetic alterations and epigenetic profiles associated with different types of gliomas. These molecular characteristics can be used to refine the classification of the glioma, improve the prediction of the results obtained with current and future treatments in patients and as a guide for a personalized treatment. Also, have a prognostic approach in each patient. This paradigm shift has modified the way glioma is diagnosed and its implications in daily practice in the indication of different treatments to the patient. Here, synthetically, we review and highlight clinically relevant molecular biomarkers. We try to capture how advances in the molecular genetics of gliomas can promote and pave the way to precision medicine in neuro-oncology